PERBANDINGAN MULTI ATTRIBUTIVE IDEAL-REAL COMPARATIVE ANALYSIS DAN TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION PENILAIAN EVALUASI KINERJA KECAMATAN - Arm, Ashyoka Inca; Harmayani, Harmayani (Smart Education, 2025)
Abstract: Facing competition in the global era, organizations are required to work more efficiently and effectively. Increasingly tight competition means that organizations must be able to increase their competitiveness in order to maintain the survival of the organization. Every organization is required to display excellent performance in various fields, especially those related to its stakeholders. The current increasingly complex environmental situation requires an organization to be able to satisfy the interests of various stakeholders. Evaluate sub-district performance. The aim of the research is to analyze a sub-district performance evaluation assessment system using the MAIRCA and TOPSIS methods. The data used in this research is secondary data on sub-district performance in a certain period which is related to improving coordination, accountability and professionalism of government administration in the sub-district. The output results from a sub-district performance evaluation assessment system using the MAIRCA and TOPSIS methods have different results in conducting assessments, the MAIRCA method produces a ranking with a value for Silau Laut District of (0.00733333), Pulau Rakyat District (0.011), Pulo Bandring District (0.0118333) , Tanjung Balai District (0.0125), Air Joman District (0.0125) and so on. Meanwhile, in the TOPSIS method, in first place are Pulau Rakyat District (0.775665), Silau Laut District (0.767506), Air Joman District (0.741373), Tanjung Balai District (0.718545), Aek Kuasan District (0.6731). Keywords: Comparison, MAIRCA, TOPSIS, Performance Evaluation Assessment, District. Abstrak: Menghadapi persaingan di era global, organisasi dituntut untuk bekerja lebih efisien dan efektif. Persaingan yang semakin ketat menyebabkan organisasi harus mampu meningkatkan daya saing dalam rangka menjaga kelangsungan hidup organisasi. Setiap organisasi dituntut untuk menampilkan kinerja yang prima dalam berbagai bidang, terutama yang terkait dengan para stakeholdernya. Situasi lingkungan saat ini yang semakin kompleks menuntut sebuah organisasi untuk bisa memuaskan kepentingan stakeholder yang beraneka ragam. Melakukan evaluasi terhadap kinerja kecamatan. Tujuan penelitian ialah untuk menganalisa sebuah sistem penilaian evaluasi kinerja kecamatan Menggunakan Metode MAIRCA dan TOPSIS. Data yang digunakan dalam penelitian ini ialah data sekunder kinerja kecamatan di periode tertentu yang berhubungan dengan meningkatkan koordinasi, akuntabilitas, dan profesionalitas penyelenggaraan pemerintah di Kecamatan. Hasil output dari sebuah sistem penilaian evaluasi kinerja kecamatan menggunakan Metode MAIRCA dan TOPSIS memiliki hasil yang berbeda dalam melakukan penilaian, pada metode MAIRCA menghasilkan perangkingan dengan nilai Kecamatan Silau Laut sebesar (0.00733333), Kecamatan Pulau Rakyat (0.011), Kecamatan Pulo Bandring (0.0118333), Kecamatan Tanjung Balai (0.0125), Kecamatan Air Joman (0.0125) dan seterusnya. Sedangkan pada metode TOPSIS di urutan pertama adalah Kecamatan Pulau Rakyat (0.775665), Kecamatan Silau Laut (0.767506), Kecamatan Air Joman (0.741373), Kecamatan Tanjung Balai (0.718545), Kecamatan Aek Kuasan(0.6731). Kata kunci: Perbandingan, MAIRCA, TOPSIS, Penilaian Evaluasi Kinerja, Kecamatan